Features of management and implementation of financial and economic activities of various forms and types of institutions - A. Yu. Yakovlev (Управление)
The issues of management and financial and economic activities of state, municipal and private institutions have considered in the article. Mostly in our paper we talk about state and municipal institutions, which, in contrast to private ones, are divided into types (autonomous, budget and state). Each type has a number of unique features that, depending on the situation, give it strong or weak features. The type of institution is mainly due to its scope of detail and the purpose for which it has created. The most progressive type is considered an autonomous institution. It has greater freedom of financial and economic activity (it can open not only personal accounts in the treasury, but accounts in credit institutions, purchases on the basis of regulations approved by the supervisory board, etc.) and has a collegial body represented by a supervisory board consisting of representatives of state and municipal government, workers and independent specialists. The actions of official duty institutions, created for the execution of works and the execution of state (municipal) functions are most constrained. The average «freedom» is endowed with budgetary institutions established to fulfill the state (municipal) assignment in the spheres of education, health, culture, science, social protection, employment of the population, physical culture, sports and other fields. This is the main part of kindergartens, schools, houses of culture, theaters, museums, leisure centers, sports clubs and schools, clinics, hospitals, dispensaries, higher educational institutions, scientific institutes. They are most prevalent in the Russian Federation at both the federal and regional (subjects of the federation) and municipal levels.